Journal Management at the University of Jambi: An Evaluative Study Towards an Accredited Journal: Journal Management at the University of Jambi: An Evaluative Study Towards an Accredited Journal - Hansein Arif Wijaya; Yusuf, Muhammad; Hendra, Robi (FKIP Universitas Jambi, 2025)
Scientific journals play a strategic role in ensuring the quality and reputation of higher education institutions, particularly through the national accreditation mechanism facilitated by the Arjuna portal. This study aims to evaluate journal management at the University of Jambi from the aspects of management, substance, accreditation, and indexation as a basis for strengthening governance towards meeting accreditation standards. The study uses a descriptive-evaluative approach with document analysis of the recapitulation file